Long-term visit-to-visit blood pressure variability and renal function decline in patients with hypertension over 15 years - Chia, Yook Chin; Lim, Hooi Min; Ching, Siew Mooi (Wiley Open Access, 2016)
Background: Visit‐to‐visit variability of systolic blood pressure (SBP) has been shown to contribute to cardiovascular events and all‐cause mortality. However, little is known about its long‐term effect on renal function. We aim to examine the relationship between visit‐to‐visit blood pressure variability (BPV) and decline in renal function in patients with hypertension and to determine the level of systolic BPV that is associated with significant renal function decline. Methods and Results: This is a 15‐year retrospective cohort study of 825 hypertensive patients. Blood pressure readings every 3 months were retrieved from the 15 years of clinic visits. We used SD and coefficient of variation as a measure of systolic BPV. Serum creatinine was captured and estimated glomerular filtration rate was calculated at baseline, 5, 10, and 15 years. The mean SD of SBP was 14.2±3.1 mm Hg and coefficient of variation of SBP was 10.2±2%. Mean for estimated glomerular filtration rate slope was −1.0±1.5 mL/min per 1.73 m2 per year. There was a significant relationship between BPV and slope of estimated glomerular filtration rate (SD: r=−0.16, P<0.001; coefficient of variation: r=−0.14, P<0.001, Pearson's correlation). BPV of SBP for each individual was significantly associated with slope of estimated glomerular filtration rate after adjustment for mean SBP and other confounders. The cutoff values estimated by the receiver operating characteristic curve for the onset of chronic kidney disease for SD of SBP was 13.5 mm Hg and coefficient of variation of SBP was 9.74%. Conclusions: Long‐term visit‐to‐visit variability of SBP is an independent determinant of renal deterioration in patients with hypertension. Hence, every effort should be made to reduce BPV in order to slow down the decline of renal function.